Metagenomic next-generation sequencing (mNGS) for diagnostically challenging infectious diseases in patients with acute leukemia - Garnica,Marcia (2021)
ABSTRACT This report shows the contribution of next-generation metagenomic sequencing (mNGS) as an alternative to challenging diagnostic infection in immunosuppressed individuals. Herein, we report three acute leukemia patients who developed severe invasive infections due to different etiologies: fungi, viruses, and protozoa. mNGS improved the diagnosis of the infections and provided the opportunity for adequate therapy. The mNGS is a hypothesis-free diagnostic platform, increasing potential in challenging diseases in hematological patients due to the extended diagnostic panel and the expedite access to the result.